Service Sector in India-Growth and Opportunities in Higher Education: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper aims to get an overview of service sector in India and to know growth opportunities in higher education. The service sector is one of the important sectors economies in three sector model. India ranks 15 in the service sector. The service sector in India comprise wide range of activities such as financial, business process outsourcing services, transportations, real estate, instructions, hospitality among many others. Now the Indian higher education is at a cross road. The growth of India’s higher educational institution has been spectacularly rapid. The number of enrollmentt has become more doubled.